Comparative characterization of gum rosins for their use as sustainable additives in polymeric matrices (2022)
There is a growing interest in the use of non-polluting compounds, which come from renewable sources, and which performance in their scope is equivalent to their synthetic similes. In this work, five types of rosins from different sources were studied, verifying the existence of differences that can be inferred in their subsequent use and application as material additives. For the study, rosins were analyzed using gas-mass chromatographic techniques, infrared spectrophotometry (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and color characterization. The results showed that the samples are composed of either abietic acid or by its structural isomers in contents higher than 80%. FTIR shows that the main difference in the gum rosins is related to the proclivity to absorb environmental moisture and that this technique is not enough to differentiate them. Moreover, the DSC reveals that the gum rosins present enthalpy relaxation effects due to their manufacturing process. The TGA showed that gum rosins are thermally stable until 200°C, therefore they can be successfully blended with thermoplastic polymers. Finally, the color characterization shows little differences between the samples, being CA the gum rosin with the greatest total color differences.